How do you solve this using quadtratic formula? (7x-2)^2=4

1 Answer
Mar 8, 2018

See method to obtain equation in form ax^2+bx+c=0

Explanation:

First expand out the brackets:
(7x-2)^2 = (7x-2)*(7x-2)=49x^2-28x+4

in the original equation, we had a 4 on the right hand side, and we need a zero to apply the quadratic formula, so we subtract 4 from both sides, giving:

49x^2-28x+4-4=4-4
=>49x^2-28x=0
a factor of 7 can be taken out to leave:
=> 7x^2 -4x=0

Then the quadratic formula can be applied where a=7, b=-4 and c=0

x=(-b±sqrt(b^2-4ac))/(2a)

You can also solve easily without quadratic formula:
Factorise:
x(7x-4)=0

Two solutions:
x=0 and 7x-4=0

The latter leads to x= 4/7